Problem Based Learning on Textbook Accounting Indonesia Adaptation: A Content Analysis Approach - Janwarin, Xaverius M Y (FKIP Universitas Lampung, 2018)
Abstract: Problem based learning in textbook Accounting Indonesia Adaptation: A content analysis approach. Objectives: This study aims to develop the Problem based learning method in the Accounting Indonesia Adaptation textbook as a suggestion for developing critical thinking and solving problems in accounting. The solution to problems in problem series Aand B is done to meet the learning objectives in each chapter. Methods: Implementation of the problem based learning method using content analysis in the accounting textbook through several stages, namely, finding a problem, identifying and analyzing the problem and conducting a synthesis and application of the analysis of transactions and the implementation of the accounting cycle both manually and computerized. Findings: These results canbe presented and reflected as a learning experience and help the formation of critical thinking skills and problem solving in the development of accounting. Conclusions: It is important to compile textbooks orreferences by including cases or problem-based questions that require problem solving.Keywords: Problem based learning, content analysis, textbook Accounting Indonesia AdaptationDOI: http://dx.doi.org/10.23960/jpp.v8.i2.201808